Image tagging and gearing resources applied to students' graphic material. Learning techniques in pursuit of inclusiveness for urban and landscape design. - López Baez, Jesús; Carrasco Hortal, José (My University, 2020)
Inclusiveness can be considered a requirement for contemporary statements in urban and landscape design referring to age, condition, gender or nature. But how is inclusiveness influenced by spatial design? Can this relation be measured or proven? And more precisely, which interactions are considered across different generations or between human and non-human agents? This paper describes student’s work evaluation procedures through a methodology consisting of selecting picture-based content from initial reference materials provided by teaching staff, as well as graphic material designed and produced by the students, to further analyze these through data visualization techniques and the production of info-graphics. In a latter step, a gearing game – which is a type of sociogram used to understand agents and matters of interest – is utilized to drive a discussion about design statements for further stages of development concerning students’ design projects. The first stages of the methodology are strongly influenced by how the students perceive elements from reference materials and represent these in their own design productions. A literature review further investigates the dichotomy between representation and perception, and the generation of subjective images. As a final consideration, this work aims to create combined methodologies by incorporating participatory observation methods (e.g. photovoice and flow charts) from the social sciences into urban and landscape design, as they are understood through an accurate design of the learning experience. Similarly, non-representational design and dataviz diagrams from urban and landscape design could potentially be implemented in the teaching of social sciences.
Keywords: Raumplanerausbildung; Planerausbildung; Bildmaterial; Lehrmaterial; Lernprozess